PENINGKATAN KEMAMPUAN SISWA DALAM MENYAMPAIKAN GAGASAN MELALUI METODE DISKUSI KELOMPOK PADA SISWA KELAS V DI SDI UTASEKO - Fransiska Saveriana Ndek; Pelipus Wungo Kaka (Jurnal Komunikasi, 2026)
The aim of this research is to improve students' ability to convey ideas through the application of the group discussion method. The focus of this research is fifth grade students at SDI Utaseko, who in initial observations showed limitations in conveying ideas in a structured and confident manner. This research uses a classroom action approach with two cycles. Each cycle includes planning stages, action implementation, observation and reflection. Data was collected through observation, interviews, and tests on students' ability to express ideas. The focus of this research is: discussion methods in improving students' ability to convey ideas. This improvement can be seen from students being able to work together in discussions, being responsible for providing ideas, and participating in concluding the results of discussions. The increase in the ability to convey ideas occurred in the second cycle after implementing learning using the group discussion method, there were 6 students or 27.27% who had grades categorized as very high, 13 students or 59.09% who had grades categorized as high, 3 students or 13.63 had grades who categorized as sufficient, 1 student or 4.54% was categorized as very poor and no students had a score in the very poor category. Meanwhile, classically the average score for measuring students' ability to convey ideas is 82.22%, which means that the average student is in the high category. Thus, the group discussion method was effectively used in improving the ability to convey ideas to class V students at SDI Utaseko.